A Rare Presentation of First Branchial Cleft Cyst in an Adult Female: A Case Report and Review - .J, Sai Avinash; Manikandan, Vinisha; Dheenadhayalan, M.; Karthickeyan, K.; .Shanmugasundaram, P; Sri, M.K.Sundar (Journal of Neonatal Surgery, 2025)
Branchial cleft cysts are congenital epithelial cysts resulting from the failure of obliteration of the branchial clefts during embryonic development. They often present as painless, fluctuant swellings in the lateral aspect of the neck and may lead to complications such as infection or compression of nearby structures if left untreated. This case report outlines the diagnosis, surgical management, and postoperative care of a 34-year-old female patient presenting with a left-sided neck swelling, later diagnosed and excised as a branchial cyst. The physical examination and imaging studies, including ultrasound and CT scan, suggested a first branchial cleft cyst. Fine needle aspiration cytology supported the diagnosis by revealing benign cystic contents. The goal of treatment is to achieve complete surgical excision of the cyst to prevent recurrence and associated complications.